Impact of rotavirus vaccination on rotavirus hospitalizations in Taiwanese children. Issue 49 (3rd December 2021) - Burke, Rachel M.; Shih, Shuman; Hsiung, Chao Agnes; Yen, Catherine; Jiang, Baoming; Parashar, Umesh D.; Tate, Jacqueline E.; Wu, Fang-Tzy; Huang, Yhu-Chering
Highlights: Rotavirus is a leading cause of severe pediatric gastroenteritis worldwide. In Taiwan, two rotavirus vaccines were licensed in 2006, but coverage is suboptimal. Rotavirus hospitalizations declined significantly after vaccine implementation. Abstract: In 2006, two rotavirus vaccines were licensed in Taiwan but were not added to the national immunization schedule. National Health Insurance data from 2003 through 2017 were used to compare rotavirus-associated pediatric hospitalizations before and after vaccine introduction. Rotavirus hospitalization rates among children < 5 years of age significantly declined by 24% (95% confidence interval [CI] 23 – 25%) in post-vaccine compared to pre-vaccine rotavirus seasons. Rotavirus hospitalization rates declined by 42% (95% CI 39 – 44%) among infants < 12 months of age, and by 38% (95% CI 36 – 40%) among children 12 – 23 months of age. These findings suggest that, despite not being included in the national immunization schedule, rotavirus vaccines had a measurable impact on reducing rotavirus hospitalization burden among Taiwanese children.